(untitled) (Biological Sciences - PJSIR, 2024)
The aim of this study is to identify sugarcane genotypes that combine high yield and stability across environments to identify best potential cultivars of sugarcane for a region during the years 2017- 18 and 2018-19. Fourteen sugarcane genotypes under varietal development programme of Sugarcane Research Institute, Faisalabad were evaluated in two different locations of northern region in Punjab, Pakistan for their yield response and stability in that ecology, The research trials was carried out in randomized complete block design with three replicates. The sugarcane genotype S2005-US-54 stand best performer by achieving cane yield of 122 t/ha and sugar yield of 15.52 t/ha at Bhalwal, while sugarcane genotype CPF-253 and CPF-252 produced high cane yield of 129 t/ha, 125 t/ha and sugar yield of 16.69 t/ha, 15.25 t/ha at Chelianwala respectively. The adaptability and stability studies of fourteen genotypes concluded that CPF-253, S2005-US-54, CPF-252 produced the highest cane yield of 123.5 t/ha, 121.5 t/ha, 115t/ha respectively and most of the productive genotypes being high yielding ability was best suited for planting in northern agro-ecologies in Punjab.